Martin Barré - Estenger, Max ca. 20./21.Jh; Fish, Julia 1950- (ER Publishing, 2020)
ER Publishing first launches a book collection titled TRANSATLANTIQUE dedicated to artist writings and their invaluable perspectives. Each book is devoted to an American or European artist active primarily in the second half of the 20th century. All the contributions are from artists living on the other side of the Atlantic. They add their perspectives to the critical discussion on the featured artist's practice. Each book is edited by a Guest Editor who is an important actor of the art world and has a great knowledge of the featured artist. A major figure in French abstraction of the late 20th century, Martin Barré (1924-1993) probed the fundamental parameters of painting for five decades. During the last 15 years, his work has received increasing attention in the United States. For Transatlantique, Molly Warnock brings together six American artists who share their invaluable perspectives on this decisive work
Keywords: Barré, Martin -- 1924-1993; Malerei; Aufsatzsammlung